HUBUNGAN POLA ASUH ORANG TUA DENGAN KECANDUAN DRAMA KOREA DI KALANGAN MAHASISWA (PENILITIAN DI UNIVERSITAS IBN KHALDUN KOTA BOGOR) - Sidik, Sahrul Noval; Rahman, Imas Kania; Asmahasanah, Salati (EDUTECH CONSULTANT, 2019)
This study aims to determine whether there is a relationship between parenting parents who are addicted to Korean Drama. This type of research is quantitative research. The population in this study were all students of Ibn Khaldun University (UIKA) Bogor. The sample of this study is those who like Korean Drama with 100 samples. In this study the research instrument used a questionnaire with a Likert scale. Analysis of the data used is the validity and reliability test. After calculating the Pearson correlation obtained rxy 0.208. The index 0.00-0.20 means that there is a positive correlation between the variables X and Y which includes the WEAK or LOW correlation between parenting and addictions to Korean drama. It turned out that the 5% significant level was obtained by r Table 0.195. Thus at the significance level of 5% rxy = 0.208> r Table 0.195 means that the alternative hypothesis (Ha) is accepted.